Nonlinear Pedagogy and the implications for teaching and training in table tennis - Larissa Rafaela Galatti; João Cláudio Machado; Mairin Del Corto Motta; Milton Shoiti Misuta; Taisa Belli
Abstract Aim: It is to propose a game-based and player-centred approach to teaching table tennis using nonlinear pedagogy insights. Methods: This is an essay which offers a well-reasoned articulated nonlinear pedagogy perspective on coaching and teaching table tennis issues Results: It offers the description of a propose based on a player-centred and game-based approach for table tennis supported by nonlinear pedagogy, illustrating examples of how to apply nonlinear pedagogical principles to design representative learning tasks in order to adapt them to learners' skills level. Conclusion: A novel perspective for teaching and training table tennis is presented here and we intend that this proposal may help coaches to design an effective learning environment.